Empire in British Girls' Literature and Culture - Smith, M. author. aut Link
XI, 207 p.
Keywords: While the gender and age of the girl may seem to remove her from any significant contribution to empire, this book provides both a new perspective on familiar girls' literature, and the first detailed examination of lesser-known fiction relating the emergence of fictional girl adventurers, castaways and 'ripping' schoolgirls to the British Empire.